Synergizing Ventures - Ufuk Akcigit; Emin M. Dinlersoz; Jeremy Greenwood; Veronika Penciakova (Center for Economic Studies and ifo Institute (CESifo), 2019)
Venture capital (VC) and growth are examined both empirically and theoretically. Empirically, VC-backed startups have higher early growth rates and initial patent quality than non-VC-backed ones. VC-backing increases a startup's likelihood of reaching the right tails of the firm size and innovation distributions. Furthermore, outcomes are better for startups matched with more experienced venture capitalists. An endogenous growth model, where venture capitalists provide both expertise and financing for business startups, is constructed to match these facts. The presence of venture capital, the degree of assortative matching between startups and financiers, and the taxation of VC-backed startups matter significantly for growth.
Keywords: G24; N20; O30; 330; venture capital; assortative matching; endogenous growth; IPO; management; mergers and acquisitions; research and development; startups; synergies; taxation; patents